STUDY OF THE BIODEGRADATION OF RESIDUES OF LUBRICANT OIL RETINED IN BENTONITA USING THE BACTERIAL OIL EATING MICROBES CONSORTIUM (Rodhococus, Pseudomonas and Bacillus) - Chirre Flores, Jaqueline (2018)
The inadequate final disposal of hazardous industrial waste, such as bentonite used in the refining processes of contaminated automotive lubricants, generates a series of negative environmental impacts on water, air and soil resources. To contribute to the minimization of these impacts, the purpose of the present investigation was to evaluate the biodegradation capacity of a sample of automotive lubricating oil trapped in bentonite clay, using the bacterial consortium Oil Eating Microbes (Rodhococus pyridinivorans, Pseudomonas montielli and Bacillus sp.). To obtain the maximum performance of the biodegradation of the oil (reduction of total hydrocarbons of oil in the clay), by the bacterial consortium, two experimental tests were carried out, in a five liter capacity bioreactor, where the concentration of biodegradation of total petroleum hydrocarbons was measured, the first was performed for 13 days and the second in 59 days: less than 2 % and 50% yields were obtained for the first and second tests respectively, which shows the reduction of contamination of the contaminated bentonite clay, which is one of the environmental problems that it is desired to eliminate, since they cause air, water or soil pollution, affecting the ecosystems both aerial, aquatic or terrestrial.